Impacts of Invasive, Exotic Grasses on Quail of Southwestern Rangelands: A Decade of Progress? - William P. Kuvlesky Jr.; Leonard A. Brennan; Timothy E. Fulbright; Fidel Hernandez; Steven J. DeMaso; Joseph P. Sands; Robert M. Perez; Jason B. Hardin (National Quail Symposium Proceedings, 2017)
Exotic grass invasions are a serious concern for State and Federal agencies, non-government organizations, and private landowners engaged in quail conservation and management. Quail biologists recognized the potential negative impacts of exotic grass invasion on North American quail populations 2 decades ago. This issue was addressed in a review paper published in the Proceedings of the 5th National Quail Symposium in 2002. That paper reported the state of our knowledge on impacts of exotic grass invasions on 5 quail species inhabiting southwestern rangelands. Our objective is to update the progress of exotic grass-quail research on southwestern rangelands during the past decade by reviewing studies that provide specific results about the impacts of exotic grass invasions on southwestern quail populations. Results of studies that have quantified the impacts of exotic grass on quail habitat use are summarized and discussed along with studies that describe how exotic grasses impact important components of quail habitat such as diversity and abundance native herbaceous plants and arthropods. Management of exotic grasses is also discussed.
Keywords: exotic; fire; grass; herbicide; invasion; management; quail; range; southwest